Financial Management System Of Pujaselera Multistand Restaurant - Fadillah, Sofyan Rinandi, Umi Fadlillah, ST. MEng, Endah Sudarmilah, S.T., M.Eng (2013)
Pujaselera is a kind of restaurant which is located in front of Muhammadiyah University of Surakarta. It is a kind of restaurant which is based on multi stand system. This restaurant contains some stands which sell some different foods. In maintaining the restaurant, the manager of Pujaselera Resrtaurant still uses paper-based system. One of the main problems of this system occurs at chashier and calculate the income which will be devided. If it uses paper-based, so it will take long time. Finance system is intended to facilitate and to solve in increasing the serving to the customer and the seller. It is also intended to make the report of Pujaselera restaurant becoming more clearly. The program of finance system is done by using application Lazarus and data base that is used MySql.while Fortes Report is used to make a report. In this research, it has been built a system of finance management in Pujaselera restaurant which makes the process of entering the sale data by using desktop application becoming more accurately.